Efficient regeneration system for rapid multiplication of clean planting material of Ensete ventricosum (Welw.) Cheesman - Tripathi, J.N.; Matheka, J.; Merga, I.; Gebre, E.; Tripathi, L. (Springer, 2017)
Enset (Ensete ventricosum (Welw.) Cheesman) is an economically important staple food crop in Ethiopia, especially in the southern and southwestern regions. It is called “false banana” due to its resemblance to banana, but inability to produce any edible fruit. The crop is clonally propagated using field-grown suckers. This study reports the development of a robust regeneration technique to propagate large numbers of plantlets using corm discs containing intercalary meristematic tissues. Hundreds of shoot buds were induced from corm discs of enset cultivar ‘Bedadeti’ cultured on Murashige and Skoog (MS) medium supplemented with 1.5 mg L−1 2,4-dichlorophenoxyacetic acid, 0.216 mg L−1 zeatin, and 2 g L−1 activated charcoal. The shoot buds were regenerated into complete plantlets when transferred onto MS medium supplemented with 1 mg L−1 6-benzylaminopurine and 2 g L−1 activated charcoal. More than 100 plantlets were generated in 4 mo from corm discs isolated from a single in vitro mother plantlet. Well-rooted plantlets were acclimatized in soil with 100% success, and did not show any apparent phenotypic abnormalities under glasshouse conditions. This efficient regeneration system could be very useful for the rapid multiplication of clean pathogen-free planting material.